Impact of healthcare inequities on survival in Mexican patients with metastatic renal cell carcinoma - Bourlon, Maria T.; Remolina-Bonilla, Yuly A.; Acosta-Medina, Aldo A.; Saldivar-Oviedo, Bruno I.; Perez-Silva, Antonio; Martinez-Ibarra, Nayeli; Castro-Alonso, Francisco Javier; Martín-Aguilar, Ana E.; Rivera-Rivera, Samuel; Mota-Rivero, Fernando; Pérez-Pérez, Perla; Díaz-Alvarado, María G.; et al. (Frontiers in Oncology, 2023)
Introduction The survival of patients with metastatic renal cell carcinoma (mRCC) has improved dramatically due to novel systemic treatments. However, mRCC mortality continues to rise in Latin America. Methods A retrospective, multicenter study of patients diagnosed with mRCC between 2010-2018 in Mexico City was conducted. The aim of the study was to evaluate the impact of healthcare insurance on access to treatment and survival in patients with mRCC. Results Among 924 patients, 55.4%, 42.6%, and 1.9% had no insurance (NI), social security, (SS) and private insurance (PI), respectively. De novo metastatic disease was more common in NI patients (70.9%) compared to SS (47.2%) and PI (55.6%) patients (p<0.001). According to IMDC Prognostic Index, 20.2% were classified as favorable, 49% as intermediate, and 30.8% as poor-risk disease. Access to systemic treatment differed by healthcare insurance: 36.1%, 99.5%, and 100% for the NI, SS, and PI patients, respectively (p<0.001). NI patients received fewer lines of treatment, with 24.8% receiving only one line of treatment (p<0.001). Median overall survival (OS) was 13.9 months for NI, 98.9 months for SS, and 147.6 months for NI patients (p<0.001). In multivariate analysis, NI status, brain metastases, sarcomatoid features, bone metastases, no treatment were significantly associated with worse OS. Conclusion OS in mRCC was affected by insurance availability in this resource-limited cohort of Mexican patients. These results underscore the need for effective strategies to achieve equitable healthcare access in an era of effective, yet costly systemic treatments.